Rural tourism in development function of rural areas in Serbia - Dašić Dejan (Ekonomika Poljoprivrede (1979), 2020)
This paper analyzes past experiences and examples of good practice in the development of rural tourism, with particular reference to the potential of Serbia. The aim of this paper is multiple. Given that rural areas in Serbia face significant economic and demographic problems, rural tourism may be one of the answers to the question of how to revitalize rural areas. Tourism development in villages of Serbia can make an important contribution to job creation but also to preserving jobs for the population and increasing their interest in staying in the region and creating new business opportunities. In addition to building a positive image, economic prosperity, by investing more in this area, Serbia could solve the problem of population migration within its territory to larger cities, as well as the departure of young people from the country.